Convolution encoder for forward error correction - Ahmad Termizi, Mohd Azmi (2010)
Nowadays bandwidth demands are totally increase and the tolerance for errors and latency decreases, designers of data-communication systems are looking for new ways to expand available bandwidth and improve the quality of transmission. One solution isn't actually new, but has been around for a while. Nevertheless, it could prove quite useful. Called forward error correction (FEC), this design technology has been used for years to enable efficient, high-quality data communication over noisy channels, such as those found in satellite and digital cellular-communications applications. The big attraction of FEC technology is how it adds redundant information to a data stream. This enables a receiver to identify and correct errors without the need for retransmission and the data will be transfer faster than ever